Association of anxiety and depressive symptoms with C-reactive protein in diverse Latinos: Results from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) - Guerrero, Lourdes R.; Hong, Suzi; Tarraf, Wassim; Perreira, Krista; Camacho, Álvaro; Kohn, Jordan N.; Jimenez, Daniel E.; Talavera, Gregory A.; Gallo, Linda; Allison, Matthew A.; Wassertheil-Smoller, Sylvia; González, Hector M. (PloS one, 2023)
High sensitivity C-reactive protein (hsCRP) is a marker of systemic inflammation that has been associated with persistent depressive symptoms. Depression and anxiety are frequently associated with a chronic inflammatory state, yet the nature of this relationship has not been rigorously examined in diverse Hispanic/Latino populations. We aimed to study the association of anxiety and depressive symptoms as well as comorbid presentations, with circulating high sensitivity C-reactive protein (hsCRP) levels in a large Latino cohort of diverse heritages. We hypothesized a significant positive associations of both anxiety and depressive symptoms and hsCRP levels and potential variations among the heritage groups. Depressive symptoms and anxiety were measured by the Center for Epidemiological Studies Depression Scale (CES-D) and State-Trait Anxiety Inventory (STAI), respectively. Serum hsCRP (hsCRP) levels of 15,448 participants (age 18 to 75 years; 52.3% women) from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) were measured and categorized based on the established cardiovascular disease (CVD) risk reference values (< 1mg/L, low; 1-<3 mg/L, intermediate; ≥ 3mg/L, high). Mean CES-D, STAI scores, and hsCRP levels were 7.0 (SD = 5.9), 17.0 (SD = 5.7), and 3.84 (SD = 7.85), respectively. Generalized linear modeling, adjusted for sociodemographic characteristics revealed significant associations between depression (exp(β) = 1.12; p<0.01) and anxiety symptoms (exp(β) = 1.10; p<0.05) with continuous hsCRP levels. For categorical values of hsCRP, one SD increase in CES-D and STAI scores was associated with a 10% and 8% increase in the RRRs of high vs. low hsCRP, respectively. However, these relationships between CES-D or STAI and hsCRP were no longer statistically significant after adjustment for CVD risk factors and medications. We found modest associations between anxiety and depressive symptoms and systemic inflammation measured by hsCRP among diverse Hispanics/Latinos that did not appreciably differ between heritage groups.